Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Corrigendum to “Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model” [J. Hydrol. 662 (2025) 133909] - Donald J. Martin; Richard G. Niswonger; R.Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2026)

Estimating irrigation consumptive use for the conterminous United States: coupling satellite-sourced estimates of actual evapotranspiration with a national hydrologic model - Donald J. Martin; Richard G. Niswonger; R. Steve Regan; Justin L. Huntington; Thomas Ott; Charles Morton; Gabriel B. Senay; MacKenzie Friedrichs; Forrest S. Melton; Jonathan Haynes; Wesley Henson; Amy Read; et al. (Journal of Hydrology, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

The Influence of Biological Maturity on Dynamic Force–Time Variables and Vaulting Performance in Young Female Gymnasts - Sylvia Moeskops; Jon L. Oliver; Paul J. Read; John B. Cronin; Gregory D. Myer; G. Gregory Haff; Isabel S. Moore; Rhodri S. Lloyd (Journal of Science in Sport and Exercise, 2020)
Purpose This cross-sectional study investigated dynamic force–time variables and vaulting performance in young female gymnasts of different maturity status. Methods 120 gymnasts aged 5–14 years were sub-divided into maturity groupings using percent of predicted adult height (%PAH) attained. Participants performed three jumping protocols, the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ), before completing straight jump vaults that were recorded using two-dimensional video. Results Jumping performance improved with biological maturity evidenced by the most mature gymnasts’ producing significantly more absolute force ( P < 0.05; all d > 0.78), impulse ( P < 0.05; all d > 0.75) and power ( P < 0.05; all d > 0.91) than the least mature group, resulting in the greater jump heights ( P < 0.05; all d > 0.70). While, no significant differences were observed in relative peak force across multiple tests, measures of relative peak power did significantly increase with maturity. Based upon regression analyses, maturation was found to influence vertical take-off velocity during vaulting, explaining 41% of the variance in each jumping protocol. Across all tests, the DJ was found to have the highest predictive ability of vaulting vertical take-off velocity, explaining 55% of the total variance. Conclusion Biological maturation impacts jump height and underpinning mechanical variables in young female gymnasts. Vaulting vertical take-off velocity appears to be influenced by maturation and various dynamic force–time variables, particularly those during DJ, which had the highest explained total variance.

Metabolic rhythms in flowing waters: An approach for classifying river productivity regimes - Philip Savoy; Alison P. Appling; James B. Heffernan; Edward G. Stets; Jordan S. Read; Judson W. Harvey; Emily S. Bernhardt (Limnology and Oceanography, 2019)
Although seasonal patterns of ecosystem productivity have been extensively described and analyzed with respect to their primary forcings in terrestrial and marine systems, comparatively little is known about these same processes in rivers. However, it is now possible to perform a large‐scale synthesis on the patterns and drivers of river productivity regimes because of the recent sensor advances allowing for near‐continuous estimates of river productivity. Here, we explore a dataset of 47 U.S. rivers to examine whether there are characteristic river productivity regimes. We use classification approaches to develop a typology of productivity regimes and then use these regimes to examine differences with respect to potential controls of productivity. We identified two distinct metabolic regimes, which we named Summer Peak and Spring Peak Rivers , within our dataset. These regimes meaningfully differed in both the timing and magnitude of productivity and were robust to different approaches to classification. We also found that several variables, including watershed area and characteristics of water temperature or discharge, were able to predict the class membership of these regimes with modest accuracy. Our results support the presence of characteristic metabolic regimes and suggests that these regimes may have common sets of environmental controls. We present classification as one approach to begin exploring the productivity regimes of rivers. The strength of our approach is that it fully leverages these newly available high‐frequency productivity estimates to create classes that can be used to draw inferences about how the controls of river productivity differ between or within systems.

Survey of Citrus tristeza virus (CTV) on Citrus paradisi (Macfad.) cv. “Marsh” in South Africa - D. A. Read; M. F. Palacios; J. Figueroa; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

Survey of Citrus tristeza virus (CTV) diversity in pigmented Citrus x paradisi (Macfad.) (Grapefruit) trees in north-western Argentina - D. A. Read; M. F. Palacios; J. Kleynhans; J. Figueroa; L. Foguet; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Survey of citrus tristeza virus (CTV) strains in Citrus x limon (L) Burm f. (lemon) in Tucumán Province, Argentina - D. A. Read; M. F. Palacios; J. Figueroa; L. Foguet; J. Kleynhans; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Widespread omnivory and low temporal and spatial variation in the diet of fishes in a hydrologically variable northern Australian river - B. J. Pusey; A. H. Arthington; B. Stewart‐Koster; M. J. Kennard; M. G. Read (Journal of Fish Biology, 2010)
This article examines the trophic ecology of freshwater fishes (22 species in 15 families) in a wet and dry tropical Australian river of high intra‐annual and interannual hydrological variability. Seven major trophic groups were identified by cluster analysis; however, four food items (filamentous algae, chironomid larvae, Trichoptera larvae and Ephemeroptera nymphs) comprised almost half of the average diet of all species. The influence of species, fish size, spatial effects and temporal effects on food use was investigated using redundancy analysis. Size, time and space accounted for little of the perceived variation. Ontogenetic changes in diet were minor and limited to a few large species. Spatial variation in trophic composition of the fish assemblages reflected the effects of the Burdekin Falls and dam, a major geographic barrier, on species distributions. Little spatial variation in diet was detected after accounting for this biogeographical effect. Temporal variations in flow, although marked, had little effect on variations in fish diet composition due to the low temporal diversity of food resources in physically monotonous sand and gravel channels. Species identity accounted for

Leptotrichia endocarditis: Report of two cases from the International Collaboration on Endocarditis (ICE) database and review of previous cases - L. B. Caram; J. P. Linefsky; K. M. Read; D. R. Murdoch; T. Lalani; C. W. Woods; L. B. Reller; S. S. Kanj; M. M. Premru; S. Ryan; M. Al-Hegelan; P. Y. Donnio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Macrobenthic polychaete assemblages of the continental shelf and upper slope off the west coast of the South Island, New Zealand - P. K. Probert; G. B. Read; S. L. Grove; A. A. Rowden (New Zealand Journal of Marine and Freshwater Research, 2001)
Polychaete assemblages are described from replicate box‐core samples collected in summer 1983 at 18 stations on the continental shelf and upper slope (28–943 m) off the west coast of the South Island, New Zealand, south‐eastern Tasman Sea (c. 41–43°S, 169–172°E). Three main station groupings were identified by multivariate analysis: (1) inner shelf sandy stations characterised by Prionospio australiensis, Aricidea (Acesta) sp., Magelona cf. dakini, Paraprionospio aff. pinnata, Aglaophamus sp., Heteromastus filiformis , and Magelona sp.; (2) middle to outer shelf muddy stations characterised by Levinsenia cf. gracilis, Prionospio australiensis, Paraprionospio coora, Aglaophamus verrilli , and Auchenoplax mesos; and (3) upper slope sandy mud or mud stations characterised by Prionospio ehlersi . A combination of water depth and sediment clay content provided the best correlation with the biotic pattern. Spionidae was the most abundant family (49% of polychaete individuals), which may reflect the scope for opportunistic species in a shelf environment characterised by a high input of terrigenous sediment and episodic upwelling.

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)